Blockchain technology for operational excellence and supply chain resilience : a framework based on use cases and an architecture demonstration - Shahzad, Khuram; Helo, Petri; Ranta, Mikko; Nousiainen, Essi (Taylor & Francis, 2024)
Increased risks and uncertainties can disrupt the whole supply chain (SC), resulting in ineffective value transition. Facilitated by digital technologies, SC resilience can be achieved which enables organisations to strengthen capabilities. Therefore, blockchain is emerging as a promising technology that promises transparency and decentralisation across multiple SC nodes and can effectively respond to any disruption and recover fast through visibility. However, prior research does not offer a clear framework for blockchain adoption to achieve operational excellence and SC resilience. This paper develops an explanatory framework for SC resilience and operational excellence by conducting a rigorous analysis of recent literature, existing industrial cases (i.e. food SC, diamond SC, electric vehicle (EV) battery SC, blood SC), and a reference architecture implementation in forest SC. We explore how blockchain has addressed the traceability challenges and developed operational excellence in selected use cases. The theoretical and use case analysis reveal the promising effect of blockchain in developing capabilities and effective response systems where transparency, traceability, real-time information sharing, process, and security are the most common value propositions. The reference model (available on GitHub) demonstrates an increase in process efficiency by offering data safety, and transparent and traceable information which cannot be altered throughout SC.
Keywords: Blockchain; Supply chain ecosystem resilience; Operational excellence; Reference model; blockchains; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Tuotantotalous|en=Industrial Management|